Implementasi Alat Musik Keyboard sebagai Media Pembelajaran Seni Budaya Materi Bernyanyi Secara Unisono SMP Negeri O Mangunharjo - Rama Daniansyah; Olan Yogha Pratama (Universitas Palangka Raya, 2024)
This research aims to explain the use of the keyboard as a media for learning arts and culture, material for singing in unison and to teach students how to sing correctly and precisely according to the notation using keyboard media in class VII at SMP Negeri O Mangunharjo. This research includes Classroom Action Research (Action Research Classroom) which was carried out in 2 cycles with planning, implementation, observation and reflection stages. Data will be collected through observation. The research instruments used were tests and field notes. Data analysis in this research uses quantitative descriptive techniques carried out through the scoring stage. Data is validated using process, outcome, democratic, catalytic and dialogic validity. Efforts to improve singing techniques using media keyboard As a learning medium, singing in unison can increase student learning achievement. This has been proven in the results of the average score for students, before the implementation of this action was carried out, a score of 67.11 was obtained, then after entering the first cycle stage it could increase to 69.66 and after cycle II it increased again to 74.50. Even though the results obtained from the average were not very significant, in cycle II it was found that several students scored in the